To combine the expression \((3/10x - 3) + (1/10x + 8)\), we will first distribute and then combine like terms.
-
Distribute the terms in each parenthesis: \[ = \frac{3}{10}x - 3 + \frac{1}{10}x + 8 \]
-
Combine the like terms (the terms with \(x\) and the constant terms):
- For the \(x\) terms: \[ \frac{3}{10}x + \frac{1}{10}x = \frac{3 + 1}{10}x = \frac{4}{10}x = \frac{2}{5}x \]
- For the constant terms: \[ -3 + 8 = 5 \]
-
Combine both results: \[ = \frac{2}{5}x + 5 \]
So, the final simplified expression is: \[ \frac{2}{5}x + 5 \]